Penentuan Interval Waktu Pemeliharaan Mesin untuk Mereduksi Downtime di Departemen Produksi PT. X - 10070219059, Muhammad Gaos Nafitullah; Nita P.A Hidayat; Ajrina Febri Suahati (UNISBA Press, 2024)
Abstract. PT X is engaged in the manufacturing industry of car spare parts production by implementing a Make To Order (MTO) market response strategy. The company often experiences damage to machine components and causes downtime. Based on this, it has an impact on the Company's losses, namely targets that are not achieved and product defects, to reduce these losses, improvements are made by maintaining engine components. In this study, the planned maintenance method is used which is a maintenance method. Based on the background that has been described, the problem formulations in this study are: